Chronic cumulative risk assessment of the exposure to organophosphorus, carbamate and pyrethroid and pyrethrin pesticides through fruit and vegetables consumption in the region of Valencia (Spain). (March 2016) - Quijano, Leyre; Yusà, Vicent; Font, Guillermina; Pardo, Olga
Abstract: In the present study, the chronic cumulative exposure to organophosphorus (OPs), carbamates (CBs) and pyrethroid and pyrethrin (PPs) pesticides in the region of Valencia through fruit and vegetables consumption is presented. A total of 752 samples and 84 pesticides were studied of which, 52 were OPs, 23 CBs and 9 PPs. Residue data were derived from the Valencia Region monitoring program 2007–2011 and food consumption levels from a questionnaire-based dietary survey conducted in 2010 in the same area. The relative potency factor (RPFs) approach was used to estimate chronic cumulative dietary exposure to OPs, CBs and PPs using acephate, oxamyl and deltamethrin as index compounds, respectively. The exposure was estimated using a deterministic approach and two scenarios were assumed for left-censored results: the lower-bound (LB) scenario, in which unquantified results (below the limit of quantification (LOQ)) were set to zero and the upper-bound (UB) scenario, in which unquantified results were set to the LOQ. Results demonstrate that the chronic exposure of the young (<16 years) and adult (≥16 years) population to pesticides through fruits and vegetables is under control (even at high or frequent consumption of fruits and vegetables), for the three groups of pesticides. Highlights: Chronic cumulative exposure to pesticides in Valencia through fruit and vegetable consumption is presented. Risk assessment contributes to improve food safety and to built public confidence in the way risk is assessed. Results demonstrate that the chronic cumulative exposure via fruit and vegetable consumption is under control.